Analisis Program Klinik Bisnis untuk Perkembangan UMKM Kota Malang - Irawan, Erfan; Mohammad Wildan Aminullah; Nizar Aditya Arifin (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The Business Clinic Program by the Department of Cooperatives, Industry, and Trade (Diskopindag) of Malang City is a strategic initiative aimed at strengthening Micro, Small, and Medium Enterprises (MSMEs) through need-based training, intensive mentoring, financing facilitation, legal assistance, and product promotion. The program not only focuses on improving technical capabilities but also encourages entrepreneurial mindset shifts to adapt with market dynamics and digital technology. One of its main strengths is the tutor system, where each tutor assists five MSMEs intensively for a year. Furthermore, cross-sector collaboration and a data-driven evaluation approach make the program measurable and impactful. As a result, many MSMEs experience increased sales, improved production efficiency, and are able to access modern markets and export opportunities. Despite facing challenges such as limited access to finance and digitalization gaps, this program serves as a comprehensive and inclusive empowerment model that can be replicated by other regions as part of sustainable local economic development strategies.